Achieving equitable access to health technologies during a pandemic: Lessons learned from UK universities’ technology transfer practices & policies 2019–2023 - Ayolola Eni-Olotu; Rebecca Hotchkin; Rachel McCormick; Molly Pugh-Jones; Sarai Mirjam Keestra (Global Public Health, 2025)
The COVID-19 pandemic underlined stark inequalities in timely access to health technologies worldwide. Universities, by conducting a significant amount of early biomedical research and development, have a critical but often overlooked role in determining downstream equitable access to health technologies. This paper reviews university's policies and practices regarding COVID-19 health technologies in the United Kingdom (UK) during the recent pandemic using annual freedom of Information (FOI) requests between 2019 and 2023 to a cohort of 35 UK universities and website searches. We provide an overview of all patents and licenses filed for COVID-19 technologies, changes in technology transfer policies or strategies, and engagement with international mechanisms designed to enhance equitable transfer of knowledge and intellectual property rights during the pandemic. Despite a time-limited increase in non-exclusive licensing of COVID-19 health technologies at the height of the pandemic, there was a lack of systemic change in university policies for technology transfer, and limited to no engagement with international mechanisms to promote equitable access. Universities can promote global equitable access to health technologies by publishing clear technology transfer policies, attaching conditions to technology transfer agreements, increasing transparency, and engaging with non-exclusive licensing mechanisms, now and in future health emergencies.